Motivation in Words: Promotion- and Prevention-Oriented Leader Communication in Times of Crisis. (September 2018) - Stam, Daan; van Knippenberg, Daan; Wisse, Barbara; Nederveen Pieterse, Anne
Research demonstrates that situational uncertainty or crisis strongly influences the endorsement of the more charismatic or decisive leadership styles and that inspirational communication is at the heart of these styles. However, there is currently little understanding of what leaders should convey through their communication to be endorsed in crisis. Based on regulatory focus theory, we argue that times of crisis make leaders who use more promotion-oriented communication more likely to be endorsed and leaders who use more prevention-oriented communication less likely to be endorsed. Results of Study 1, an archival study of U.S. presidents, show that presidents who use more promotion-oriented communication are more endorsed but only if economic growth is low or if inflation is high, while no effects of the use of prevention orientation of communication surfaces. Results of Study 2, a laboratory experiment, show that leaders who communicate a promotion orientation, as compared to a prevention orientation, motivate higher performance in participants in a crisis condition, but that there is no difference in a no-crisis (i.e. control) condition. Finally, results of Study 3, a scenario experiment, demonstrate that organizational leaders that communicate more promotion-oriented (as opposed to more prevention-oriented) have a higher chance of being endorsed but only in times of crisis and that this effect is mediated by followers' motivation to realize the plans of the leader.